THE HOME NETWORK: AN AUSTRALIAN NATIONAL INITIATIVE FOR HOME THERAPIES1. Issue 1 (7th March 2013) - Chow, Josephine; Fortnum, Debbie; Moodie, Jo‐Anne; Simmonds, Rosemary; Tomlins, Melinda
SUMMARY: Background: Longer, more frequent dialysis at home can improve life expectancy for patients with chronic kidney disease. Increased use of home dialysis therapies also benefits the hospital system, allowing for more efficient allocation of clinic resources. However, the Australian and New Zealand Data Registry statistics highlight the low uptake of home haemodialysis and peritoneal dialysis across Australia. Objective: In August 2009, the Australia's HOME Network was established as a national initiative to engage and empower healthcare professionals working in the home dialysis specialty. The aim was to develop solutions to advocate for and ultimately increase the use of home therapies. This paper describes the development, achievement and future plan of the Australian HOME Network. Achievements: Achievements to date include: a survey of HOME Network members to assess the current state of patient and healthcare professional‐targeted education resources; development of two patient case studies and activities addressing how to overcome the financial burden experienced by patients on home dialysis. Future projects aim to improve patient and healthcare professional education, and advocacy for home dialysis therapies. Conclusion: The HOME Network is supporting healthcare professionals working in the home dialysis specialty to develop solutions and tools that will help to facilitate greater utilisation of home dialysis therapies.